Engaging university casual tutors in collaborative reflection for improving student learning outcomes. Issue 4 (4th July 2017) - Bentley-Williams, Robyn
Abstract: There is a growing trend in universities to rely on casual tutors to fill the shortfall in permanent teaching staff. However, casual tutors often feel marginalised and excluded from having a voice in designing unit improvements. This research analyses five casual tutors' perspectives on their teaching, learning, and assessing role. Data were gathered through reflective processes and semi-structured interviews. The research project and findings provide a collaborative model for capturing their input and feedback at critical points in the unit delivery and marking process. The results identify tutors' insights, concerns, and underlying principles informing their roles. This investigation highlights the importance of listening to casual tutors' voices. Their views can inform new ways of looking at issues, leading to enhanced student learning and progressing quality teaching.